(3OSJhQ GddZIs - (3CHh YHO Gddg HOjY GdReGf GdMSjf Hf EHQGgje GdfWJQi GdCUHgGfj GdedbH HPi GddSGfjfs
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY GdYGde HbOQJg hHYO , agPG OSJhQ GddZI GdYQHjI GdeSJYedI GdeYJeOI GdeCKhQI GdhGQOI ai cJGH Gddg JYGdi s
(3BNQgG (B:s
(3hMQha GdaGQSjI SJI hYTQhf jLeYgG bhdg hGdMQha GdJi dG JONd GdaGQSjI KeGfjIjLeYgG aEf de jLOgG adjWdHgG ai GdCOhGJ hGdCHhGH GdKdGKI GdeJbOeI GdJi UOQHgG GdcJGH hbO TgO GdCFeI HGTJeGdg Ydi LejY GddZI GdeTghQI s
(3HChdgG Jedc jYhO Edi SfI (B1141 (3g`s
(3hai UdH GdfU CdaGX hLed aGQSjIs
(3HgG fXGe GdJYbjHIs
(3bSeI Ydi (B28 (3cJGHG HYOO GMQha ai cd cJGH (B12 (3HGHG HYOO TghQ GdSfI s
(3fSNI KGfjI s
(3bQf GdfSN (B:s
Keywords: (3GddZIs